Organizational and Economic Regulation of the Grain Market in Conditions of Sustainable Development - LYSHENKO, M. O.; MAKARENKO, N. O.; MAKAROVA, V. V.; MUSHTAY, V. A. (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018DO - 10.14505//jemt.v9.1(25).12, 2018)
Based on the retrospective analysis, the necessity of state regulation of the grain market in the conditions of sustainable development is proved in the article. The priority directions of improvement of organizational and economic regulation of sustainable development of agricultural production are offered and the degree of development of each element of the infrastructure of the agrarian market, their mutual influence on the development of the agrarian sector is determined.